Анализа корелације нивоа серума NT-прo-BNP, IGFBP-7 и CTRP12 код пацијената са хроничном срчаном инсуфицијенцијом: Нивои серума NT-прo-BNP, ИГФБП-7 и ЦТРП12 код хроничне срчане инсуфицијенције - Fan, Zhen; Huang, Heng; Hua, Hejuan; Chen, Lin; Wang, Laoji; Yan, Jierou; Zhao, Fei (Journal of Medical Biochemistry, 2025)
Objective: To investigate serum N-terminal pro-brain natriuretic peptide (NT-pro-BNP), insulin-like growth factor binding protein-7 (IGFBP-7), and C1q tumor necrosis factor-related protein 12 (CTRP12) levels and significance in patients with chronic heart failure (CHF).Methods: The CHF group consisted of 116 CHF patients who received care at this hospital between October 2023 and March 2025. The patients were classified into Grade II (47 patients), Grade III (41 patients), or Grade IV (28 patients) based on the heart function classification of the New York Heart Association (NYHA). The control group consisted of 64 healthy patients who were examined physically in the hospital throughout the same time period. Using multivariate logistic regression, the factors impacting MACEs in patients with congestive heart failure were examined. Through the use of the receiver operating characteristic (ROC) curve, researchers were able to assess the predictive power of blood NT-pro-BNP, IGFBP-7, and CTRP12 for MACEs in chronic heart failure patients.Results: Comparing the CHF group to the control group, the LVEDD increased, the LVEF and serum CTRP12 decreased, and the levels of NT-pro-BNP, IGFBP-7, Hcy, and hs-CRP climbed (P
Keywords: Ц1к туморски некрозни фактор-повезани протеин 12; Хронична срчана инсуфицијенција; IGFBP-7; NT-pro-BNP